(untitled) (Studia Prawnicze / The Legal Studies, 1981)
While analysing the structure of legal foundations of spatial planning - besides inner coherence of this structure (and its conformity with the rest of the legal system), also practice of planning should be taken into account as far as its conformity with respective legal norms is concerned. Functioning of the organs of planning in practice constitute a relatiVely autonomous system, sometimes inconsistent with legal norms which themselves are not always coherent. This lack of coherence may result from the fact that these norms were created in various, periods of time, and also from the fact that conditions of their implementation (e.g. territorial division of the country) have undergone some changes. Legal foundations of spatial planning (meaning the sources of law) are dispersed. Statutory model of planning was in a way corrected in connection with the reform of territorial devision. This was done by way of two legal acts of the Council of Ministers, although issues concerning adjudication of spatial conflicts and formulating principles of spatial policy are considered exclusively statutory matters. In resolutions of the Council of Ministers of July 9, 1976 no 148 and of December 29, 1977 no 196 a "real" model of spatial planning was formulated, where one can encounter various kinds of plans totally unknown to the law on spatial planning. In particular, plans of macroregions, simplified plans of the communes, as well as programs of development of certain branches of national economy have no legal force whatsoever. The issue of stability of decisions concerning local spatial plans gains particular importance in connection with judicial control of administrative decisions. In the domain of spatial policy (e.g. real estate commerce, expropriation, agri’culture, forestry, etc.), while deciding the issue of conformity of the appealed decision with the law on the basis of article 196 [1] § 1 of the law of Jaunary 31, 1980 (Journal of Laws on 9 entry 26), the Chief Administrative Court will have to consider local plans, since only in reference to these Plans criteria of legality of a given decision could be determined. However, presupposing stability of socio-economic aims in the domain of spatial planning we should expect high effectivity of legal means after the ammendment of the law on spacial planning, taking into consideration all the consequences of the administrative and territorial reforms.